The Conceptual Framework of Human Resource Management Practices Effects on Employee Performance: A Study Among Palestinian Municipalities Employees - Omar Jamil Ahmed Muqedi; Khairunneezam Mohd Noor; Safiyyah Ahmad Sabri (International Journal of Multidisciplinary Research in Science, Engineering, Technology & Management, 2024)
Non-Indexed Publication